Análise da disciplina de educação ambiental e valorização do espaço local nos estabelecimentos de ensino do município de Bom Jesus do Sul - PR - Opolski, Carolina Albertoni (2016)
This research aims to analyze the practices in environmental education based on the discipline of 'Environmental Education and appreciation of Local Space' existing schools in the municipality of Bom Jesus do Sul-PR and EA practices carried out in other schools and municipalities that do not belong to disciplinary proceedings in their curricula. The survey was conducted in schools / colleges of three municipalities: Francisco Beltrão, Santa Izabel do Oeste and Bom Jesus do Sul- PR, these were surveyed six different establishments (State College Field Paulo Freire, State College Guilherme de Almeida, State School Marquês de Maricá, State of the Field School San Pedro, State College Bom Jesus and Field State School XV de Novembro). We use questionnaires to teachers and students, being thirty (30) questionnaires answered by teachers of 06 (six) establishments surveyed and 63 (sixty-three) questionnaires answered by students. We ask in relation the practice in environmental education, the skills about the concepts and legislation and laws that permeate the environmental education materials, among others questions that enable an analysis about the reality of environmental education practice in establishments in comparision the environmental education realized in school of the Bom Jesus do Sul-PR that have specific discipline. Also, we realized an interview with manager, teachers and students who participate of the discipline of 'Environmental Education and appreciation of Local Space, in which we can understand the development of the discipline and content teaching, relating with the theoretical knowledge. From these instrumentes, we can diagnose the practice of the environmental education of teachers, students and the manager's vision that has one action of the environmental education through discipline in your school. We support research on the theoretical understanding from the development of a reflection on the landscape; the cartesianism; the environmental education (especially the manufacturing and / or critical), and the curriculum, understanding the results of the research realized an to diagnose the data compiled. Among the others authors used we can mention Albanus, Leff, Loureiro, Lima, Sacristan, Moreira, and others. About the results obtained, we can point out that teachers who have training in undergraduate inserted in sciences area, have an easier time developing the EA. Another the feature is the predominance of the development of EA classified as Traditional in establishments surveyed. Finally, our conclusion reveals that the discipline of 'Environmental Education and appreciation of Local Area' can be considered as a guaranteed space for the development of EA, more comprehensive than in the other surveyed establishments develop EA cross or interdisciplinary way . We point out that inclusion of the discipline of Environmental Education and Local Area Valuation was carried out taking into account characteristics of the city of community Bom Jesus do Sul- PR, the main instrument the school garden, with menu dedicated to the discipline of geography. In cases guided by the research, we consider that EA as a discipline, has superior result, but has limitations, because according to the disciplinary curriculum requires knowledge and content from other disciplines, barrier implemented more effectively in the transverse and/or interdisciplinary methodology. Discipline is a space for discussion and development of EA, but that can be accomplished in other ways as complementary activities in contraturno or as a curriculum component. We conclude with positioning not in of the existence of a specific discipline by the survey results.